2018
DOI: 10.15376/biores.13.2.2187-2203
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Hybrid Short Path Evaporation to Concentrate Lactic Acid and Sugars from Fermentation

Abstract: Lactic acid is an important organic compound that finds various applications in the chemical, pharmaceutical, food, and medical industries. Many of these applications require lactic acid with high purity. Hybrid short path evaporation (HSPE) is a separation process well studied in the petrochemical sector that is mainly used to obtain compounds with high purity. It is also a process offering small residence time, low pressure, and environmentally friendliness. The concentration process of lactic acid was studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(24 citation statements)
references
References 13 publications
2
22
0
Order By: Relevance
“…The generated vapour from each step, first condenses and then feeds the upstream evaporator. [63] Aspen simulations on this section demonstrated that this purification unit is sensitive to deviations in operating conditions because any failure in this section directly affects the quality or quantity of the final product.…”
Section: Discussionmentioning
confidence: 97%
“…The generated vapour from each step, first condenses and then feeds the upstream evaporator. [63] Aspen simulations on this section demonstrated that this purification unit is sensitive to deviations in operating conditions because any failure in this section directly affects the quality or quantity of the final product.…”
Section: Discussionmentioning
confidence: 97%
“…plastics (i.e., polylactic acid (PLA)) (Demichelis et al, 2017). Recent market estimates have forecast significant growth in the demand for LA over the coming years due to its applicability in multiple industries and the role it plays in the production of PLA (Biddy et al, 2016;Castro-Aguirre et al, 2016;Alves de Oliveira et al, 2018;Ranjan and Baghel, 2018).…”
Section: Figurementioning
confidence: 99%
“…LA is a promising high-value intermediate produced during the pre-fermentation stage of two-stage AD and has been the focus of a few recent studies (Kim et al, 2016;Bastidas-Oyanedel and Schmidt, 2018;Demichelis et al, 2018;Bühlmann et al, 2021;Bühlmann et al, 2022a;Bühlmann et al, 2022b;Chenebault et al, 2022). LA (C 3 H 6 O 3 ) is a three-carbon organic acid which is generally sold as an 88 wt% solution which is expected to experience significant market growth to 1,960 kton by 2024/ 2025 valued at USD 9.8 billion (Alves de Oliveira et al, 2018;Presswire, 2018). The price of LA generally follows the price of starch and sugar feedstocks, and recently has reached around 3.0-4.0 USD•kg −1 (Alves de Oliveira et al, 2018).…”
Section: Anaerobic Production Of Lactic Acidmentioning
confidence: 99%
See 2 more Smart Citations